The current state of the law in Poland: the Family Planning Act and its interpretation - Przebierała, Weronika (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
The chapter interprets the Act of 7 January 1993 on family planning, protection of the human foetus, and the conditions of permissibility of terminating a pregnancy, Poland's main act protecting the life of a conceived child. Abortion is permitted only where pregnancy threatens the woman's life or health, or likely resulted from a prohibited act, limited to the twelfth week in that case.Drawing on the literature and Constitutional Tribunal jurisprudence, the chapter shows that the only exception to protecting the right to life is its conflict with another person's same right, and that Polish law recognizes no "right to abortion." It analyses sanctions under the Criminal Code, abortion tourism, and criminal-law protection of a child surviving an abortion.Practices observed in Europe and globally suggest a child can be killed after birth without consequence for the abortionist; statutory exceptions never apply once a child is born.